2019
DOI: 10.3389/fphy.2019.00152
|View full text |Cite
|
Sign up to set email alerts
|

Single Electron Memory Effect Using Random Telegraph Signals at Room Temperature

Abstract: We show a manipulation of a single electron at room temperature by controlling Random Telegraph Signals (RTSs) by voltage pulses. Our silicon nanowire triple-gate transistor exhibited RTSs when potential barriers were electrically created by two of the three gates. From the statistics of the signals, we optimized the voltage pulse such that a single electron was intentionally captured in the potential well, and the retention time of approximately 10 ms was observed in this memory operation. This study indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(104 reference statements)
1
3
0
Order By: Relevance
“…Unlike in all metal/insulator/metal devices previously studied, if the bias is held constant a cyclical filament formation and disruption at random times occurs (see Figure 5b). More importantly, the mean on/off current ratio statistically observed in Figure 5b is >100, which is the highest ever reported in the literature for a random signal of telegraphic characteristics when compared not only to other reports on h‐BN [ 12,37,47,54 ] but also TMOs, [ 11,52,55,67–72 ] ultra‐scaled transistors [ 73–78 ] and nanowires [ 79–87 ] (see Figure 5c). This behavior, which remains stable over time, cannot be strictly called RTN because this term has been always employed in the literature to refer to charge trapping and de‐trapping, while here it is related to ionic movement; hence, we propose to call it random telegraph signal (RTS)‐like current.…”
Section: Resultssupporting
confidence: 50%
“…Unlike in all metal/insulator/metal devices previously studied, if the bias is held constant a cyclical filament formation and disruption at random times occurs (see Figure 5b). More importantly, the mean on/off current ratio statistically observed in Figure 5b is >100, which is the highest ever reported in the literature for a random signal of telegraphic characteristics when compared not only to other reports on h‐BN [ 12,37,47,54 ] but also TMOs, [ 11,52,55,67–72 ] ultra‐scaled transistors [ 73–78 ] and nanowires [ 79–87 ] (see Figure 5c). This behavior, which remains stable over time, cannot be strictly called RTN because this term has been always employed in the literature to refer to charge trapping and de‐trapping, while here it is related to ionic movement; hence, we propose to call it random telegraph signal (RTS)‐like current.…”
Section: Resultssupporting
confidence: 50%
“…By applying Green's non-equilibrium function approach [5][6][7], the CBPD for a lowconductance SET was calculated [4] and referred to as a weak coupling regime [8][9][10]. Utilizing the proposed method, one can determine the optimum temperature to operate a low-conductance SET for various applications, such as single-electron memory [11][12][13] and quantum dots [14], which trap and manipulate individual electrons, allowing researchers to explore quantum phenomena. Meanwhile, a high-conductance SET, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29,31 ] For instance, it has been demonstrated that a single electron captured in a single‐trap state responsible for an RTS behaves quantum mechanically, and such a trap can thus be considered a promising candidate for use in quantum information computing. [ 32,33 ] Moreover, an important role of single traps has been shown for digital processing systems and memory devices. [ 34 ] These opportunities offered by an electrically active single trap in nanoscale devices attract the increasing interest of the scientific community.…”
Section: Introductionmentioning
confidence: 99%